Innovative Practice of Multimodal Teaching Mode in English Education and Teaching Practice in Colleges and Universities in the New Media Era - Peng, Peilan; Gao, Xianyi; Wang, Juan (Applied mathematics and nonlinear sciences, 2024)
Traditional English teaching methods are increasingly seen as outdated, failing to adequately develop students’ language abilities. This study introduces a multimodal teaching approach, evaluated through the innovative use of the sailfish optimization algorithm to gauge student attitudes towards this educational innovation. Additionally, the study leverages a genetically optimized CARMA algorithm to analyze academic achievement data, identifying optimal strategies for enhancing learning outcomes. Results indicate a significant improvement in students’ oral English skills, with approximately 70% reporting progress and 86 students endorsing the multimodal approach. Post-implementation test scores across five classes showed an impressive range of 85-97, with Classes A and B demonstrating significant score improvements (p-values of 0.021 and 0.014, respectively). The successful application of this novel teaching method in collegiate settings underscores its potential for broader adoption and highlights its relevance for modernizing educational practices across various subjects.